Official Financing for Developing Countries 1997. (World Economic and Financial Surveys; World Economic and Financial Surveys ;, 1998)
This study provides information on official financing for developing countries with the focus on low and lower-middle-income countries. It updates the 1995 edition and reviews developments in direct financing by offical and multilateral sources. Topics of interest include external debt sustainability for heavily indebted poor countries; new official financing flows to developing countries; developments in export credits;financing from multilateral institutions; debt restructuring by official bilateral creditors; plus, numerous appendices.